The Effect of Health Education Through Video Media on Adolescent Knowledge About Anemia During Menstruation at SMPN 11 Makassar in 2024 (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Adolescence, between the ages of 10–19 years, is a transitional stage marked by various physical and psychological changes. These changes can lead to several health issues, one of which is anemia. Anemia is a condition in which hemoglobin levels decrease, reducing the body’s ability to transport oxygen effectively and potentially affecting overall health and productivity. According to the 2018 Riskesdas data cited in Risky Amalia’s research (2023), the prevalence of anemia in Indonesia is still high at 32%, indicating that 3 to 4 out of every 10 adolescents are affected. Female adolescents are particularly vulnerable to anemia due to menstrual blood loss, which increases the risk of iron deficiency. This study aimed to determine the effect of health education delivered through video media on knowledge about anemia during menstruation among female adolescents at SMPN 11 Makassar in 2024. The research used a quasi-experimental approach with a one-group pre-test and post-test design. The population consisted of 91 female students, with 48 selected as the sample using the Slovin formula. Participants were given educational material through video media, and their knowledge was measured before and after the intervention. The analysis results showed a statistically significant improvement in knowledge scores, with a p-value of 0.000 (<0.05), indicating that video-based health education had a substantial effect on increasing understanding of anemia during menstruation. This finding suggests that video media can be a powerful educational tool, combining visual and auditory elements to enhance learning and retention. Health education through video media is recommended as an effective strategy to increase adolescent awareness and understanding of anemia prevention and management, particularly among female students in the school setting. Such approaches can contribute to better adolescent health outcomes and reduce the prevalence of anemia in the community.